2022
DOI: 10.1016/j.molmet.2021.101423
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of ORMDL3 impairs adipose tissue thermogenesis and insulin sensitivity by increasing ceramide generation

Abstract: Objective Genome-wide association studies identified ORMDL3 as an obesity-related gene, and its expression was negatively correlated with body mass index. However, the precise biological roles of ORMDL3 in obesity and lipid metabolism remain uncharacterized. Here, we investigate the function of ORMDL3 in adipose tissue thermogenesis and high fat diet (HFD)-induced insulin resistance. Methods Ormdl3 -deficient ( Orm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
2
18
1
1
Order By: Relevance
“…For instance, sphingolipid levels were found to be unchanged in transgenic Ormdl3 overexpression and whole-body Ormdl3 KO mice, and this observation was recapitulated in HEK cells (17). However, many studies report some effect of Ormdl3 overexpression or deletion on systemic sphingolipid levels with minor changes to rodent health measures (14, 18, 19). For example, while absence of Ormdl3 has been associated with increased levels of sphingolipids within the brain, Ormdl3 knockout mice appeared metabolically healthy and similar to control mice (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, sphingolipid levels were found to be unchanged in transgenic Ormdl3 overexpression and whole-body Ormdl3 KO mice, and this observation was recapitulated in HEK cells (17). However, many studies report some effect of Ormdl3 overexpression or deletion on systemic sphingolipid levels with minor changes to rodent health measures (14, 18, 19). For example, while absence of Ormdl3 has been associated with increased levels of sphingolipids within the brain, Ormdl3 knockout mice appeared metabolically healthy and similar to control mice (19).…”
Section: Discussionmentioning
confidence: 99%
“…ORMDL3 has been implicated in a variety of disorders including asthma, inflammatory bowel disease, and obesity (8,(11)(12)(13). Recently, it was reported that mice with a whole-body knockout of Ormdl3 when challenged with cold exposure or HFD exhibit impaired regulation of brown adipose tissue thermogenesis, white adipose tissue browning, and insulin resistance (14). Yet the contribution of β-cells to the systemic glucose homeostasis remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In genome-wide association studies, the SPT suppressor ORMDL3 was identified as an obesity-related gene, and its expression in human subcutaneous WAT inversely correlates with BMI [ 235 , 236 ]. Conversely, Ormdl3 -deficient mice show elevated ceramide levels in WAT, increased body weight gain upon high-fat diet feeding, and insulin resistance, which was attributed to decreased thermogenesis and impaired WAT browning [ 235 ].…”
Section: Relevant Tissues Of Ceramide Metabolism and Action In Obesitymentioning
confidence: 99%
“…In genome-wide association studies, the SPT suppressor ORMDL3 was identified as an obesity-related gene, and its expression in human subcutaneous WAT inversely correlates with BMI [ 235 , 236 ]. Conversely, Ormdl3 -deficient mice show elevated ceramide levels in WAT, increased body weight gain upon high-fat diet feeding, and insulin resistance, which was attributed to decreased thermogenesis and impaired WAT browning [ 235 ]. Myriocin treatment reversed the detrimental phenotypes in these mice, indicating that the inhibition of ceramide synthesis by ORMDL3 is a critical mechanism for maintaining adipose tissue function and systemic energy homeostasis [ 235 ].…”
Section: Relevant Tissues Of Ceramide Metabolism and Action In Obesitymentioning
confidence: 99%
See 1 more Smart Citation